FENOMENA CUSTOMER STRESS DALAM INTENSI BELI PRODUK SMARTPHONE - Olyvia Ririmasse; Tono Mahmudin (Fakultas Ekonomi dan Bisnis Universitas Pattimura, 2017)
Recently the phenomenon of customer stress is a condition that happened in business reality. Consumer confuses and stress in planning and considering any smartphone that will be bought. It caused by some factor, like product assortment and information overload. Consumer who is stress can influence the low buying intention of consumer on any product. Beside that a lot of information is not easier consumer to make any choice of some. Thus, this research is done to analyze the influence of product assortment and information overload to the customer stress and buying intention. Data were got by questionnaire, which used purposive sampling method, with criteria, as follow: sample was people who visited hand phone store and had buying intention of that. The analysis is frequency distribution analysis, t test and regression linear. The analysis denote that product assortment has positive and significant to the customer stress, information overload has positive and significant to the customer stress, and customer stress has positive and significant influence to the buying intention.Key word: Buying intention, customer stress, product assortment and information overload